tính.
\(\sqrt[-0.4]{\left(-0,4\right)^2}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có :
\(M=\frac{7\ln\left(\sqrt{2}+1\right)^2-64\ln\left(\sqrt{2}+1\right)-50\ln\left(\sqrt{2}+1\right)^{-1}+2}{-3lg5-lg\left(10^{-1}.2^3\right)+6lg\left(10^{-\frac{1}{3}}.2^{\frac{2}{3}}\right)+4lg\left(10.5\right)}\)
\(=\frac{2}{lg5+1-3lg2-2+4lg2+4}=\frac{1}{2}\)
\(i,\sqrt{12,1.360}=\sqrt{12,1}.6\sqrt{10}=6.\sqrt{12,1.10}=6.\sqrt{121}=6.\sqrt{11^2}=6.11=66\)
\(k,\sqrt{0,4}.\sqrt{6,4}=\sqrt{0,4.6,4}=\sqrt{\dfrac{64}{25}}=\dfrac{\sqrt{8^2}}{\sqrt{5^2}}=\dfrac{8}{5}\)
\(l,-0,4.\sqrt{\left(-0,4\right)^2}=-0,4.0,4=-0,16\)
\(m,\sqrt{2^4.\left(-7\right)^2}=\sqrt{4^2}.\sqrt{\left(-7\right)^2}=4.7=28\)
i, \(\sqrt{12,1\cdot360}=\sqrt{4356}=\sqrt{66^2}=66\)
k, \(\sqrt{0,4}.\sqrt{6,4}=\sqrt{0,4\cdot6,4}=\sqrt{\dfrac{64}{25}}=\sqrt{\dfrac{2^6}{5^2}}=\dfrac{2^3}{5}=\dfrac{8}{5}\)
l, \(-0,4\sqrt{\left(-0,4\right)^2}=-0,4\cdot\left|-0,4\right|=-0,4\cdot0,4=-\dfrac{4}{25}\)
m, \(\sqrt{2^4\cdot\left(-7\right)^2}=2^2\cdot\left|-7\right|=4\cdot7=28\)
\(=5\cdot\left(\dfrac{2}{5}-\dfrac{13}{12}\right):\left[-8\cdot\dfrac{11}{8}\right]\)
\(=5\cdot\dfrac{-41}{60}\cdot\dfrac{-1}{11}=\dfrac{205}{60\cdot11}=\dfrac{41}{132}\)
\(a,\sqrt{0,1^2}=0,1\)
\(b,\sqrt{\left(-0,4\right)^2}=|-0,4|=0,4\)
\(c,-\sqrt{\left(-1,7\right)^2}=-|-1,7|=-1,7\)
\(d,-0,5\sqrt{\left(-0,5\right)^4}=\frac{-1}{2}\sqrt{[\left(\frac{-1}{2}\right)^2]^2}=-\frac{1}{2}.\left(\frac{1}{2}\right)^2=\frac{-1}{2}.\frac{1}{4}=\frac{-1}{8}\)
\(e,\sqrt{\left(1-\sqrt{2}\right)^2}=|1-\sqrt{2}|=\sqrt{2}-1\)
\(g,\sqrt{\left(\sqrt{3}-1\right)^2}=|\sqrt{3}-1|=\sqrt{3}-1\)
Lời giải:
\(\sqrt[-0,4]{(-0,4)^2}=\sqrt[-0,4]{\frac{4}{25}}=(\frac{4}{25})^{\frac{1}{-0,4}}=(\frac{4}{25})^{\frac{-5}{2}}=\frac{1}{(\frac{4}{25})^{\frac{5}{2}}}=\frac{1}{\sqrt{(\frac{4}{25})^5}}=\frac{1}{(\frac{2}{5})^5}=\frac{3125}{32}\)
\(\sqrt[-0.4]{\left(-0.4\right)^2}=\sqrt[-0.4]{\dfrac{4}{25}}=\left(\dfrac{4}{25}\right)^{\dfrac{1}{-0.4}}=\dfrac{3125}{32}\)